A rolling-mode triboelectric nanogenerator with multi-tunnel grating electrodes and opposite-charge-enhancement for wave energy harvesting - Wang, Yawei; Du, Hengxu; Yang, Hengyi; Xi, Ziyue; Zhao, Cong; Qian, Zian; Chuai, Xinyuan; Peng, Xuzhang; Yu, Hongyong; Zhang, Yu; Li, Xin; Hu, Guobiao; et al. (Nature communications, 2024)
In light of the crucial role of marine ecosystems and the escalating environmental conservation challenges, it is essential to conduct marine monitoring to help implement targeted environmental protection measures efficiently. Energy harvesting technologies, particularly triboelectric nanogenerators (TENGs), have great potential for prolonging the lifespan and enhancing the reliability of sensors in remote areas. However, the high internal resistance, low current, and friction-induced abrasion issues of TENGs limit their performance in practical applications. This work presents a rolling mode triboelectric nanogenerator that utilizes multi-tunnel grating electrodes and the opposite-charge-enhancement mechanism to harvest wave energy efficiently. The device achieves significant instantaneous and root mean square power density of 185.4 W/(m 3 ·Hz) and 10.92 W/(m 3 ·Hz), respectively. By utilizing stacked devices and an exclusively designed power management module, a self-powered ocean sensing system including computing and long-range wireless communication (0.8 km) capabilities was developed. Laboratory and in-situ ocean tests were conducted to assess and validate the system. This work offers a potential solution for the challenging deployment of marine self-powered sensing nodes. Limited current output hinders triboelectric nanogenerators for maritime applications. Authors design a rolling-mode TENG with multi-tunnel grating electrodes, achieving 185.4 W/(m 3 ·Hz) power density. They demonstrate a self-powered ocean sensing system for water quality monitoring and wireless communication.